Haemato - Biochemical Changes Following Epidural Analgesia By Upivacaine , Ropivacaine And Ropivacaine – Xylazine Combination In Goats - Ahmad, Rayees; Shukla, B.P. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was conducted on 6 healthy bucks of non descript breed weighing between 10-12 kg. Each experimental animal was subjected to 3 treatments . The haematological parameters like Hb and PCV showed significant decrease in treatment III, but there was no alteration of Hb and PCV along with other parameters such as TEC and DLC in other treatment groups. Glucose significantly increased in all the three treatment groups. ALT and BUN increased significantly only in treatment I and III. Total protein, creatinine and ALP showed significant increase in treatment III only.Bilirubin remained unchanged in all the three treatment groups.
Keywords: Lumbosacral space; Bupivacaine; Ropivacaine; Xylazine